Analisis Beban Kerja Karyawan PT XYZ Indonesia pada Bagian Insulation Menggunakan Metode Full Time Equivalent - Hikmah Sidiq Kurniawan (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
PT XYZ Indonesia is a company engaged in manufacturing by producing power transformers located in west java. In the implementation of the production process of PT XYZ Indonesia, there are sometimes problems. The problem that occurs in PT XYZ Indonesia is the production process time in the insulation section exceeds the specified target time, because the operator’s work activities are less productive, it is necessary to calculate workload in order to know the workload obtained by the operator. The purpose of this study is to level the operator workload and determine the number of workers to be optimal. Researchers used the full time equivalent method to revise the problem, by measuring the operator’s work time so that it knows the value of the workload obtained. After calculating using this method, the actual conditions at PT XYZ Indonesia have 16 operators in the insulation section, with an average value of the workload obtained is 0.34 while the recommendation of the researchers is 9 work operators in the insulation section with an average value the workload obtained is 1.06, so that it is easy to supervise the operator due to a reduction or diversion of 7 operators.